The NAIRU in theory and practice - Laurence Ball; N. Gregory Mankiw (The Johns Hopkins University, Department of Economics, 2002)
NAIRU stands for the nonaccelerating inflation rate of unemployment. It is beyond dispute that this acronym is an ugly addition to the English language. There are, however, two issues that fail to command consensus among economists, which we address in this essay. The first issue is whether the concept of NAIRU is a useful piece of business cycle theory. We believe it is, and we begin this paper by attempting to explain why. In our view, the NAIRU is approximately a synonym for the natural rate of unemployment. This concept follows naturally from any theory that says that changes in monetary policy, and aggregate demand more generally, push inflation and unemployment in opposite directions in the short run. Once this short-run tradeoff is admitted, there must be some level of unemployment consistent with stable inflation. The second issue is why the NAIRU changes over time and, in particular, why it fell in the second half of the 1990s. This question is more difficult, and the answer is open to debate. Most likely, various factors are at work, including demographics and government policies. Yet one hypothesis stands out as particularly promising: fluctuations in the NAIRU appear related to fluctuations in productivity. In the 1970s, the NAIRU rose when productivity growth slowed. In the 1990s, the NAIRU fell when productivity growth sped up. Developing and testing models that explain the links among inflation, unemployment, and productivity remains a challenge for students of business cycle theory.
Keywords: 330; Natürliche Arbeitslosigkeit; Inflationserwartung; Theorie; USA